A new genus for the American Tree Sparrow (Aves: Passeriformes: Passerellidae) - Slager, David L. (Zootaxa, 2014)
The genus Spizella (Bonaparte) contains seven species of North American sparrows in the recently resurrected family Passerellidae (Bock 1994; Barker et al. 2013), formerly placed in the Emberizidae, and includes a few of the region's most common and familiar bird species. Spizella sparrows occupy more or less open habitats; most species are at least partially migratory and form small flocks when not breeding. On the basis of their similar morphology and behavior, they have long been treated as a natural group (Ridgway 1901; American Ornithologists’ Union 1998).